Did South America foster European football?: transnational influences on the continentalization of FIFA and the creation of UEFA, 1926–1959. Issue 10 (3rd October 2017) - Vonnard, Philippe; Quin, Grégory
Abstract: UEFA was formed in Basel in June 1954, and began to take control of European football soon after its inception. It was an exceptional Pan-European organization in the context of the ongoing cold war since it almost exclusively granted memberships to football associations from Eastern Europe and the Iberian Peninsula, managing to tower above divisive ideological antagonisms. This article approaches the history of UEFA's establishment from a global history perspective. It highlights the hitherto overlooked impact of FIFA's dialogues with the South American football confederation and national associations on the creation of UEFA as a representative European institution. Firstly, it traces the South American demand for more influence on the governance of world football (especially within FIFA's committees) in the inte-rwar years, a situation that created a rift between South American and European representatives in FIFA. This confrontation arguably 'helped' the European associations to self-integrate, leaving behind their internal differences, in order to restore the hegemony they used to exercise inside FIFA before the South American dissent. Secondly, it emphasizes the role played by the South American confederation in the reorganization of FIFA in the early 1950s. Thirdly, it briefly focuses on how the South American confederation initially served as a model for the activities of UEFA.